ANALISIS KUALITAS WEBSITE E-COMMERCE BERDASARKAN PRINSIP DESAIN WEB - Tadzky Hanifah; jupriani jupriani (Universitas Negeri Padang, 2020)
The aim of this study was describe the quality of the e-commerce website based on the principles of web design in the book The Principle of Beautiful Web Design by Jason Beaird. Research determines better about the focus on design and layout design in terms of Defining Good Design, Web Page Anatomy, Grid Theory, Balance, Unity, Emphasis, Bread and Butter Layout, dan Resizing Layouts. Objects of research This is the Cotton Ink website which is an original Indonesian brand based in South Jakarta. This research will produce a picture of the quality of the composition and layout of the Cotton Ink E-Commerce website. From this review will get a good website review and can be an example for web designers and web developers in creating e-commerce websites.Researchers used descriptive qualitative methods. The data collected consists of words and images using the technique of gathering with informants. In explaining data information, researchers explain it by displaying images from the screen display of various pages on the Cotton Ink website.The results of the study can be concluded from the Ink Cotton web site that has met the criteria of a good website in the composition and layout categories that depend on the front page of several criteria that have not yet met the requirements. Based on a personal review of this web site designed by adjusting the target market of Cotton Ink products. Can be seen from the use of color, structuring content and information content in accordance with the target market for Cotton Ink products.Key words : layout and composition, web design, e-commerce, persona